MIND MAPPING: A WAY TO HONE EFL NINTH GRADERS’ WRITING SKILL AT AN ISLAMIC BOARDING SCHOOL - Yelni Erniyati (Universitas Bengkulu, 2020)
The purposes of this research were to reveal: (a) the teaching process by using mind-mapping technique, (b) the students’ writing ability. This was classroom action research which took place at Islamic Boarding School Al-Munawwaroh Bangko. The participants were ninth grade students that consisted of 23 female students in the class. This research was conducted in three cycles, and each cycle consisted of three meetings. In collecting the data, the researcher employed observation, field note, and tests. For the test, the researcher utilized writing test in the third meeting of every cycle; students were asked to write or compose the paragraph based on the given topic related to their mind map. The result showed that the teaching and learning process by using mind mapping was more interesting, and students were participated more active than before. They are enthusiastic in recalling and brainstorming the words related to the topic given. The data also indicated that there are enhancements of students’ writing after they were taught using mind-mapping technique which could be seen from the improvements of students’ score from the preliminary data to the final data. Consequently, mind mapping technique is highly recommended in teaching and in improving students’ writing.